Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.isci.2020.101384
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Co-evolutionary Pattern Suggests Targets for Pharmaceutical Intervention in the COVID-19 Pandemic

Abstract: Summary The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spillover infection in December 2019 has caused an unprecedented pandemic. SARS-CoV-2, as other coronaviruses, binds its target cells through the angiotensin-converting enzyme 2 (ACE2) receptor. Accordingly, this makes ACE2 research essential for understanding the zoonotic nature of coronaviruses and identifying novel drugs. Here we present a systematic analysis of the ACE2 conservation and co-evolution protein network across 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Additionally, a comprehensive evolutionary analysis of angiotensin-converting enzyme 2 (ACE2), the key receptor for SARS-CoV-2 entry mechanism to cell, identified that the protein is conserved across the majority of metazoan, suggesting that most metazoan is a potential reservoir for SARS-CoV-2. 29 Combined with the insight of the conservation of ACE2, our results on the evolutionary roots of genes in groups 2 and 3 suggest that the SARS-CoV-2 ability to hijack the glycosylation biosynthetic processes and ubiquitin-dependent ERAD pathway to mediate immune evasion may be conserved among metazoans. This phylogenetic profiling approach can also be used to predict the potential intermediate hosts of a viral pathogen by comparing the evolutionary roots of host cell receptor and host interactors of the essential protein of a viral pathogen.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, a comprehensive evolutionary analysis of angiotensin-converting enzyme 2 (ACE2), the key receptor for SARS-CoV-2 entry mechanism to cell, identified that the protein is conserved across the majority of metazoan, suggesting that most metazoan is a potential reservoir for SARS-CoV-2. 29 Combined with the insight of the conservation of ACE2, our results on the evolutionary roots of genes in groups 2 and 3 suggest that the SARS-CoV-2 ability to hijack the glycosylation biosynthetic processes and ubiquitin-dependent ERAD pathway to mediate immune evasion may be conserved among metazoans. This phylogenetic profiling approach can also be used to predict the potential intermediate hosts of a viral pathogen by comparing the evolutionary roots of host cell receptor and host interactors of the essential protein of a viral pathogen.…”
Section: Discussionmentioning
confidence: 60%
“…genes that are either conserved or lost as a group) are functionally related, often belonging to the same pathway (27)(28)(29)31). We have shown that both across-clade and within-clade measures of co-evolution can be informative (27,32,39), and thus we computed NPPs both across all eukaryotes ( Fig. 1A and Fig.…”
Section: Phylogenetic Profile Analysis Of Mecp2 In Eukaryotes and Mammentioning
confidence: 99%
“…Molecular evolution studies and phylogenic analysis of SARS-CoV-2 and ACE2 strongly suggest that SARS-CoV-2 might have crossed the species-specific barrier, with pangolins representing an intermediate species and bat as the main reservoir [ 24 , 25 ]. ACE2 profiling and pattern conservation analysis have displayed that it is highly conserved within vertebrates, noting that this conservation shows high divergence as the evolutionary distance increases from Homo sapiens [ 26 ]. In addition, molecular characterization and sequence alignment analysis of ACE2 show that human and non-human primates display a low evolution rate with high similarity across species except for chicken [ 27 ].…”
Section: Introductionmentioning
confidence: 99%